Da'wa Communication Model in Indonesia and Malaysia - Aziz, Abdul; Rahmah, Mishbahu; Afifah, Nisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article examines the communication models employed by Islamic preachers (da'i) in Indonesia and Malaysia, with the aim of identifying effective strategies for disseminating religious messages within different cultural and societal contexts. By comparing the da’wa (Islamic preaching) approaches in both countries, the study analyzes how cultural, religious, and social dynamics shape communication practices. It explores both interpersonal and mass-mediated communication channels to uncover their respective strengths, limitations, and implications for contemporary da’wa. The analysis also considers the challenges posed by globalization and technological advancement, emphasizing the necessity for preachers to adapt to shifting modes of communication. Ultimately, this comparative study offers critical insights into the factors that contribute to successful Islamic preaching in Southeast Asia and provides practical recommendations for enhancing the relevance and impact of da’wa across diverse audiences.